The findings related to focal asymmetry density of breast in mammography and their relationship with malignancy rate: A descriptive study in Jahrom city, 2019 - Navid Kalani; Maryam Sadat Hosseini; Zahra Mosalanezhad; Lohrasb Taheri; Marzieh Haghbeen (Mashhad University of Medical Sciences, 2023)
Mammography has diagnostic value as a tool for the early detection of intangible breast cancers, both in screening and in the detection of disease. The present study was performed with aim to evaluate the findings related to focal asymmetry density of breast and their relationship with malignancy rate. Methods: This descriptive analytical study was performed in 2019 on 150 patients with focal asymmetric density mammography referred to Khatam Al-Anbia Clinic of Jahrom city. Variables such as the appearance of the lesion on ultrasound, the presence or absence of a mass, the type of mass and the location of the lesion on ultrasound were examined and then hormonal and pathological evaluation was performed if necessary. Data analysis was done using SPSS software (version 19) and Chi-square and t-test. P<0.05 was considered statistically significant. Results: Out of 150 patients, 134 cases of focal asymmetry density (FAD) were observed on mammography. The age distribution of people whose mammographic findings showed the presence of FAD did not show a significant difference compared to patients without FAD (P=0.728). The outer upper quadrant or UOQ with 84 cases (56%) is the most common site of FAD involvement. Mammographic findings including normal, benign, suspected, borderline and malignant were significantly associated with the presence or absence of FAD (P=0.001). BI-RADS score was also significantly associated with the presence or absence of FAD in mammography (P=0.0001). The pathology was performed only for 21 cases. Based on this test, the sensitivity and specificity of focal asymmetry density for malignancy were determined as 63.64% and 20.00%. Conclusion: Considering to the sensitivity and specificity of positive focal asymmetric density in mammography, for additional studies and to increase the diagnostic value, it is necessary to use other screening methods along with mammography for patients prone to focal asymmetric density.